Processing, surface expression, and immunogenicity of carboxy-terminally truncated mutants of G protein of human respiratory syncytial virus. - Olmsted, R A (1989)
Posttranslational processing and cell surface expression were examined for three C-terminally truncated mutants of the G protein of respiratory syncytial virus expressed from engineered cDNAs. The truncated mutants, encoded by cDNAs designated G71, G180, and G230, contained the N-terminal 71, 180, and 230 amino acids, respectively, of the 298-amino-acid G protein. To facilitate detection of G71, which reacted inefficiently with G-specific antisera, we constructed a parallel set of cDNAs, designated G71/13, G180/13, and G230/13, to encode the same truncated species with the addition of a C-terminal 13-amino-acid reporter peptide which could be detected efficiently with an antipeptide serum. G71, G180, and G230 were expressed as species of Mr 7,500, 48,000, and 51,000, respectively, compared with 84,000 for parental G protein. The proteins encoded by G180 and G230, like parental G protein, contained both N-linked and O-linked carbohydrate. Also, the protein encoded by G71/13 appeared to be O glycosylated, showing that even this highly truncated form contained the structural information required to target the protein for O glycosylation. As for parental G protein, the estimated Mrs of the proteins encoded by G180 and G230 were approximately twice the calculated molecular weight of the polypeptide chain. Experiments with monensin showed that most of this difference between the calculated and observed Mr was due to posttranslational processing in or beyond the trans-Golgi compartment, presumably owing to the addition of carbohydrate or aggregation into dimers or both. Like parental G protein, all three truncated forms accumulated abundantly at the cell surface, and in each case the C terminus was extracellular. Thus, the N-terminal 71 amino acids of the G protein contained all the structural information required for efficient membrane insertion and cell surface expression, whereas the extracellular domain was dispensable for these activities. Cotton rats were immunized with recombinant vaccinia viruses expressing the G71, G180, G230, or parental G protein to compare their abilities to induce serum antibodies and resistance to challenge virus replication. The G71 and G180 recombinants failed to induce significant levels of G-specific antibodies or resistance to challenge, whereas the immunogenicity of G230 equaled or exceeded that of parental G protein. This suggested that the C-terminal 68 amino acids of the 236-amino-acid ectodomain do not contribute to the major epitope(s) of the G protein that is involved in inducing protective immunity.